The relative impact of smartwatch and smartphone use while driving on workload, attention, and driving performance. (February 2019) - Perlman, David; Samost, Aubrey; Domel, August G.; Mehler, Bruce; Dobres, Jonathan; Reimer, Bryan
Abstract: The impact of using a smartwatch to initiate phone calls on driver workload, attention, and performance was compared to smartphone visual-manual (VM) and auditory-vocal (AV) interfaces. In a driving simulator, 36 participants placed calls using each method. While task time and number of glances were greater for AV calling on the smartwatch vs. smartphone, remote detection task (R-DRT) responsiveness, mean single glance duration, percentage of long duration off-road glances, total off-road glance time, and percent time looking off-road were similar; the later metrics were all significantly higher for the VM interface vs. AV methods. Heart rate and skin conductance were higher during phone calling tasks than "just driving", but did not consistently differentiate calling method. Participants exhibited more erratic driving behavior (lane position and major steering wheel reversals) for smartphone VM calling compared to both AV methods. Workload ratings were lower for AV calling on both devices vs. VM calling. Highlights: The demands of smartwatch vs. smartphone interface use while driving were compared. Voice-based interactions had less impact than the smartphone touch interface. Apparent demand of voice-based smartwatch and smartphone interactions were similar.